Kluster Wilayah Penanggulangan Kemiskinan di Kabupaten Malang - Raharja, Firto Indra; Trivinata, Rina (Jurnal Ilmiah Administrasi Publik, 2020)
Malang Regency has a diverse socio-economic conditions and environments. It is the second largest area in East Java Province. This paper aims to examine the strategy of poverty alleviation in Malang by dividing the 33 suburbs in Malang into clusters. By doing so, the government is expected to choose the best policy strategy to reduce poverty in Malang Regency. This quantitative descriptive study used the 2018 Malang Regency in Numbers. Result show that Malang Regency is divided into three different clusters and each cluster has specific programs and activities of poverty alleviation which is adjusted to the economic potential of the suburbs. The first priority of poverty resolve is cluster 2 followed by cluster 1 and cluster 3, respectively. The proposed activities in reducing poverty are not only to improve and develop the physical quality of the settlements, but also to provide skills to the poor to improve the socio-economic conditions of the community.